2008
DOI: 10.1097/01.nnr.0000280655.58266.6c
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Comparisons Between Women With Breast Cancer and Women With a Negative Breast Biopsy

Abstract: Levels of cytokines and their patterns were markedly different in women with breast cancer as compared with those in women who did not have breast cancer. Results from this study highlight the need for further research to examine the levels and patterns of cytokines that may serve as biomarkers in clinical research. Innovations in proteomic technology have implications for expanding biobehavioral research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 26 publications
3
66
1
4
Order By: Relevance
“…BORIS may thus act as a positive regulator of hTERT transcription, and interestingly, high levels of BORIS have been detected in blood leukocytes from breast cancer patients compared with controls (27). Another observation is that the levels of a number of potentially telomerase activating cytokines, like interleukin 2 (IL-2), IL-4, IL-6, IL-7, IL-10, and IL13 (28)(29)(30)(31)(32), were found at higher serum levels in breast cancer patients compared with controls (33).…”
Section: Discussionmentioning
confidence: 97%
“…BORIS may thus act as a positive regulator of hTERT transcription, and interestingly, high levels of BORIS have been detected in blood leukocytes from breast cancer patients compared with controls (27). Another observation is that the levels of a number of potentially telomerase activating cytokines, like interleukin 2 (IL-2), IL-4, IL-6, IL-7, IL-10, and IL13 (28)(29)(30)(31)(32), were found at higher serum levels in breast cancer patients compared with controls (33).…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism of IL-8 action in estrogen receptor-negative breast cancer is largely unknown (25). The high level of IL-8 in estrogen receptor (ER) negative breast cancer cell is associated with higher invasion potential of these cells (41,42). Malonia et al reported that breast cancer cells with lacking estrogen receptor generate more interleukin-8 (34).…”
Section: Il-8 and Estrogen Receptorsmentioning
confidence: 99%
“…A few studies have documented IL10 expression in breast cancer [8][9][10][11]. Serum IL10 concentration is raised in breast cancer patients compared to normal healthy females [12], while other failed to show any association between breast cancer and serum IL10 concentration [13]. IL10 expressing tumours are often ER-ve and associated with apoptotic marker Bax, suggesting a possible aggressive behaviour of IL 10 expressing tumours [9,10].…”
Section: Introductionmentioning
confidence: 99%